Identification of Key Factors of Digital Transformation of Manufacturing companies Using Hybrid DEMATEL Method - Chu, Mingchang; Li, Bing; Yu, Xintao (Decision Making: Applications in Management and Engineering, 2024)
This study constructs the influencing factors system of digital transformation of manufacturing companies and determines the influencing factors of digital transformation of manufacturing companies from the technical level, the ability level, the environmental level in order to promote the process of digital transformation of manufacturing companies, consider the impact of technology, capacity and environment on digital transformation of manufacturing. To identify the most important factors and crucial factors, developed a model for identifying critical factors based on the hybrid DEMATEL (Decision-Making Trial and Evaluation Laboratory) methodology. Combined with the related data, this study carries out empirical analysis to demonstrate and verify the influencing factors system of digital transformation of manufacturing companies with the help of hybrid DEMATEL method. The empirical analysis results indicate that the investment share of digital technology, the benefit level of company of manufacturing industry and government support are the crucial factors, and the construction level of digital platform, the technical level of employees, level of construction of digitized equipment and industrial supporting capacity are the non crucial factors. The feasibility and validity of hybrid DEMATEL method are verified.